Re-imagining the museum : beyond the mausoleum - Witcomb, Andrea, 1965- (Museum meanings., 2003)
Re-Imagining the Museum presents new interpretations of museum history and contemporary museum practices. Through a range of case- studies, including studies from the UK, North America and Australia, Andrea Witcomb moves away from the idea that museums are always 'conservative' to suggest they have a long history of engaging with popular culture and addressing a variety of audiences. She argues that museums are key mediators between high and popular culture and between government, media practitioners, cultural policy-makers and museums professionals. The book analyses links between museums and.